Thallium underpotential deposition on silver nanoparticles: size-dependent adsorption behaviour - Campbell, F; Zhou, Y; Compton, R (2010)
We report the size-dependent adsorption of thallium on silver nanoparticles (AgNPs) in the region of underpotential deposition; the phenomenon is observed for large nanoparticles, and bulk silver, but absent for nanoparticles below 50 nm diameter. © 2010 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.